2019
DOI: 10.3390/ijerph16193641
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Protective Effects of Parental Educational Attainment on the Body Mass Index of Black and White Youth

Abstract: Background: Parental educational attainment is shown to be protective against health problems; the Minorities’ Diminished Returns theory, however, posits that these protective effects tend to be smaller for socially marginalized groups particularly blacks than whites. Aims: To explore racial differences in the effect of parental educational attainment on body mass index (BMI) in a national sample of US adolescents. Methods: In this cross-sectional study, we used baseline data of 10,701 (8678 white and 2023 bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 97 publications
1
21
0
Order By: Relevance
“…Weaker-than-expected associations of health outcomes with socioeconomic status indicators are not limited to tobacco outcomes and have been documented for diet, 73 exercise, 74 obesity, 42,75 depression, 76 anxiety, 77 self-rated health, 19,24 and health care use, 78 and have been described in children, 70 youths, 79,80 adults, 20 and older adults. 81 Similar patterns are also shown for marginalizing social identities other than race/ethnicity, 17,19,42,71,82,83 such as sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Weaker-than-expected associations of health outcomes with socioeconomic status indicators are not limited to tobacco outcomes and have been documented for diet, 73 exercise, 74 obesity, 42,75 depression, 76 anxiety, 77 self-rated health, 19,24 and health care use, 78 and have been described in children, 70 youths, 79,80 adults, 20 and older adults. 81 Similar patterns are also shown for marginalizing social identities other than race/ethnicity, 17,19,42,71,82,83 such as sexual orientation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high family SES showed a smaller effect as a preventive factor on impulsivity [59], depression [62], anxiety [64], aggression [58], grade point average (GPA) [58,65,66], and substance use [58] for AA than Caucasian children. Similarly, high SES AA youth are found to be at high risk of ADHD [67] and obesity [68]. Given the existing MDRs, it would be too optimistic and unrealistic to expect racial inequities to disappear if we could fully eliminate SES inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…In line with the Minorities' Diminished Returns (MDRs), (6,7) refer to "less than expected" health effects of family socioeconomic status, particularly parent education in ethnic minority groups compared to ethnic majority youth (8)(9)(10)(11). These patterns are persistent across SES resources and outcomes 12.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has suggested that MDRs also apply to youth. MDRs for youth are not specific to tobacco use, as they hold for a wide range of outcomes (8)(9)(10)(11). Parental education is associated with lower obesity (11,33), chronic disease (24,(34)(35)(36), aggression (24), tobacco use (24), and impulsivity (9) for Whites than for African Americans.…”
Section: Introductionmentioning
confidence: 99%